1978
DOI: 10.1590/s0071-12761978000100008
|View full text |Cite
|
Sign up to set email alerts
|

Ciclagem de nutrientes em florestas implantadas de Eucalyptus e Pinus I. distribuição no solo e na manta

Abstract: Em dois povoamentos Pinus taeda e Eucalyptus citriodora de 20 e 24 anos de idade respectivamente situados em um solo podzólico vermelho amarelo variação Laras no Município de Piracicaba, SP (22°43' lat. S, 47° 38' long. W a 580 m de altitude, preciptação média anual de 1.170 mm), foram coletadas amostras de solo, folhas e manta orgânica. Para um melhor conhecimento da mobilidade dos nutrientes as amostras foram divididas em: folhas novas, maduras e velhas, manta superior e inferior, solo superficial (0 - 10 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…There was a decrease in nutrient concentration in canopy leaves (cl), leaf fall litter (ll), and forest floor leaf litter (lf), except for Ca (Table 4). Rocha et al (1978) and Pereira et al (1984) also identified similar variation in studies with Corymbia citriodora. Thus, there is a pattern in the reduction of the nutrient concentration among photosynthetically active leaves and litter leaves accumulating on the ground.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…There was a decrease in nutrient concentration in canopy leaves (cl), leaf fall litter (ll), and forest floor leaf litter (lf), except for Ca (Table 4). Rocha et al (1978) and Pereira et al (1984) also identified similar variation in studies with Corymbia citriodora. Thus, there is a pattern in the reduction of the nutrient concentration among photosynthetically active leaves and litter leaves accumulating on the ground.…”
Section: Resultssupporting
confidence: 58%
“…The first studies addressing some nutrient cycling aspects in C. citriodora in Brazil, were carried out by Rocha et al (1978), and biomass production and nutrient export were studied by Pereira et al (1984). Recently, several studies have evaluated nutrient cycling in eucalyptus for issues related to production sustainability in short cycles (Cunha et al, 2005;Laclau et al, 2010;Diniz et al, 2011;Viera et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%